A Group of Noble Dames - Hardy, Thomas (Saga Egmont, 2023)
\'A Group of Noble Dames\' is a collection of ten short stories, framed by a central narrative. Thomas Hardy ties the tales together by presenting them as a conversation between the members of a club, in which each one tells the story of a noblewoman from the 17th or 18th Century. Through their accounts, Hardy examines a range of themes, including marriage, deceit, and social conventions. A consummate storyteller, the dialogue and characterisations are superb, allowing the reader to be drawn into each tale. \'Barbara of the House of Grebe\', one of the short stories from the collection, was later adapted for TV, starring Ben Kingsley.-